Usytuowanie ustrojowo-polityczne ochrony informacji niejawnych w Polsce, Czechach i na Słowacji - Graca, Witold; Spustek, Henryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Secret services are responsible for the system of classified information protection in Poland. In the Czech Republic and Slovakia, civil central offices operating outside the special services system have been established to perform activities in this area. Institutions dealing with the protection of classified information in the Polish political and constitutional system are mainly supervised by the executive power — the prime minister, while in the Czech Republic and Slovakia the main control factor in the system are special parliamentary committees. The protection of the rights of persons whose data are processed as part of various types of proceedings conducted by such bodies is guaranteed in all analyzed political systems by courts. In Slovakia, it is the Supreme Court. In practice, the Czech Republic and Slovakia have abandoned the separate certification system for the structures of the Ministry of National Defense. In Poland, the separation of proceedings concerning the military sphere was maintained — they are still conducted by one of the special services, Military Counterintelligence Service.
Keywords: protecting classified information; secret services; security screening